2004
DOI: 10.1097/00041433-200404000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Probing the pathways of chylomicron and HDL metabolism using adenovirus-mediated gene transfer

Abstract: New insights are provided into the role of apoE in cholesterol and triglyceride homeostasis, and of apoA-I in the biogenesis of HDL. Clearance of the lipoprotein remnants and increase in HDL synthesis are obvious targets for therapeutic interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
86
1
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 59 publications
3
86
1
4
Order By: Relevance
“…It was found that, consistent with previous findings (12)(13)(14)(15)(16), the rate of triglyceride secretion increased 6.5-fold in mice infected with adenoviruses expressing WT apoE4 as compared with mice infected with AdGFP control. In mice infected with adenoviruses expressing either apoE-mut1 or apoE4-mut2, the rate of VLDL triglyceride secretion increased 1.9-fold as compared with mice infected with the control adenoviruses but was only 27% of the rate of VLDL secretion observed in mice infected with the apoE4-expressing adenovirus (Fig.…”
Section: Apoe4-mut1 and Apoe4-mut2 Have A Modest Effect On Thesupporting
confidence: 90%
See 3 more Smart Citations
“…It was found that, consistent with previous findings (12)(13)(14)(15)(16), the rate of triglyceride secretion increased 6.5-fold in mice infected with adenoviruses expressing WT apoE4 as compared with mice infected with AdGFP control. In mice infected with adenoviruses expressing either apoE-mut1 or apoE4-mut2, the rate of VLDL triglyceride secretion increased 1.9-fold as compared with mice infected with the control adenoviruses but was only 27% of the rate of VLDL secretion observed in mice infected with the apoE4-expressing adenovirus (Fig.…”
Section: Apoe4-mut1 and Apoe4-mut2 Have A Modest Effect On Thesupporting
confidence: 90%
“…Finally, truncated apoE forms could not correct the high cholesterol profiles of the apoE Ϫ/Ϫ ϫ LDLr Ϫ/Ϫ double-deficient mice but did not induce hypertriglyceridemia, indicating that the carboxyl-terminal region of apoE is responsible for the hypertriglyceridemia (15, 16). Use of a series of apoE deletion mutants extending from amino acid 1 to amino acids 185, 202, 229, or 259 mapped the region responsible for the hypertriglyceridemia between amino acids 260 and 299 of apoE (12)(13)(14)(15)(16)(17). This region contains two hydrophobic stretches of amino acids between residues 261-269 and 276 -283.…”
Section: Apoementioning
confidence: 99%
See 2 more Smart Citations
“…The remaining particle remnants are smaller, more dense, and enriched in cholesterol esters. Low density lipoprotein (LDL) is the remnant particle of VLDL (1,2), and high plasma concentrations of LDL are associated with heart attack and stroke (3).…”
mentioning
confidence: 99%